PENGEMBANGAN MEDIA PEMBELAJARAN OFFLINE INTERAKTIF BERBASIS AUTOPLAYMEDIA STUDIO 8 UNTUK MATERI KERJASAMA DALAM BERBAGAI BIDANGKEHIDUPAN PADA SISWA KELAS VII SMP N 5 KAB. TEBO - Wulandari, Resti; Sutja, Akmal (Civic Education Perspective Journal, 2024)
The purpose of this study is to develop interactive learning media based on autoplay media studio 8 on the material of cooperation in various fields of life in PPKn learning in class VII SMP Negeri 5 Kab. Tebo. This study is a development research using the ADDIE model (Analysis, design, development, implementation, evaluation). This study develops interactive learning media. The instruments used in this study were expert team assessment questionnaires and teacher and student responses. Based on the results of the study, the results of the validation of the material on interactive learning media products with a percentage of 93%. Furthermore, media validation with a percentage of 90%. Then, validation of language experts with a percentage of 77%. And the results of the teacher response questionnaire were categorized as very practical with a percentage of 85%. While for the results of the small group trial which was categorized as very practical with a percentage of 94%. Furthermore, the results of the large group trial with a total of 22 students or one class were categorized as very practical with a percentage of 95%.